The readiness of secondary school teachers in Palestine-Nablus to adopt e-learning - Trayek, Fuad; Tunku Ahmad, Tunku Badariah; Din, Rosseni; Dwikat, Mohamad Am (2014)
This paper explored the predictors of e-learning readiness among 475 secondary school teachers in Nablus, Palestine. Multiple regression analysis was used to identify the predictors while the Rasch measurement model was used to determine the differential item functioning (DIF) across selected independent variables. Significant regression equations were found for all three aspects of readiness, while the Rasch analysis showed that age influenced the respondents' responses to the readiness items.